Anger as personality trait and physical aggression in high school adolescents - Alcázar-Olán , Raúl J. (Consorcio de Universidades Mexicanas A.C., 2015)
This study compared high and low trait anger youth (M of age = 15.92, SD = 0.9) from high school in terms of when, where and towards whom they expressed their anger in physically aggressive ways (e. g., hitting someone, hitting objects). High and low trait anger youth were those who scored in the upper (high anger, n = 125) and lower (low anger, n = 149) quartile in the Trait Anger Scale (Moscoso & Spielberger, 1999). This scale measured the anger proneness or the tendency to get angry in any place with any person. As a result, compared to low anger adolescents, those with high trait anger: 1) showed their anger with physical aggression recently toward other people (e. g., pushing someone) and toward the environment (e. g., hitting the wall); 2) throwed things to their brothers and sisters during the last month, the last week and even today: and 3) slammed their home doors throughout the day (morning, afternoon, and night). The results indicate that relationships with close persons (brothers, sisters) and the adolescents’ houses are the contexts where anger episodes emerged in greater extent, particularly in adolescents with high trait anger.